Applied linear regression - Weisberg, Sanford (New Jersey : John wiley and sons, 2014)
"Providing a coherent set of basic methodology for applied linear regression without being encyclopedic, the fourth edition of Applied Linear Regression is thoroughly updated to help students master the theory and applications of linear regression modeling. Focusing on model building, assessing fit and reliability, and drawing conclusions, the text demonstrates how to develop estimation, confidence, and testing procedures primarily through the use of least squares regression. To facilitate quick learning, this updated edition stresses the use of graphical methods in an effort to find appropriate models and to better understand them"--
Includes bibliographical references (pages 317-328) and index.
Keywords: Regression analysis; MATHEMATICS / Probability & Statistics / Regression Analysis; MATHEMATICS / Probability & Statistics / General; MATHEMATICS / Applied